2019
DOI: 10.1080/03069885.2019.1619169
|View full text |Cite
|
Sign up to set email alerts
|

Why do young people use online forums for mental health and emotional support? Benefits and challenges

Abstract: A qualitative approach was used to explore young people's experiences of using synchronous and asynchronous online forums to gain insight into the use of online services for mental health. Nineteen young people took part in two online synchronous focus groups facilitated by the online counselling service, KOOTH.com, to reflect upon the use of these two types of forum. Inductive thematic analysis indicated that forums do not replace the role of a counsellor, but they provide a valuable place for young people to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…19,20 Participating in oPTPS allows users to engage in the transference of informational and emotional support and share their experiences with others globally. 21 oPTPS has repeatedly evidenced efficacy in eradicating feelings of loneliness, breaking barriers regarding stigma, promoting self-empowerment and encouraging individuals [22][23][24] to become more active and informed patients. Individuals seeking oPTPS may believe the information they retrieve to be more trustworthy, 25 be reassured by the ease of instantaneous access to their chosen online support network, 26 reduce feelings of social isolation [27][28][29] and grant a more secure level of anonymity for the support seeker.…”
Section: Online Platforms For Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Participating in oPTPS allows users to engage in the transference of informational and emotional support and share their experiences with others globally. 21 oPTPS has repeatedly evidenced efficacy in eradicating feelings of loneliness, breaking barriers regarding stigma, promoting self-empowerment and encouraging individuals [22][23][24] to become more active and informed patients. Individuals seeking oPTPS may believe the information they retrieve to be more trustworthy, 25 be reassured by the ease of instantaneous access to their chosen online support network, 26 reduce feelings of social isolation [27][28][29] and grant a more secure level of anonymity for the support seeker.…”
Section: Online Platforms For Healthmentioning
confidence: 99%
“…Whilst opinion regarding how the media and celebrities portray mental illness was often conflicting, the general consensus from Facebook group users in this study was that there is a need for more open discussion relating to mental health to raise awareness and accurate information. 21 It is uncertain as to whether the administrators of the groups were mental health professionals. This data could not be ascertained without direct questioning which did not occur in the passive analysis.…”
Section: Facebook Support Groups For Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The online platform is a beneficial resource for those experiencing mental health issues and comprises of numerous provisions for self-regulation of one's personal mental health (McCosker, 2018). Online platforms offer accessibility to symptom checkers (Yu et al, 2019), counselling (March et al, 2018;Schlenk, 2018), peer-to-peer support Hanley et al, 2019) social media support groups (Radovic, Landsittel, Stein & Miller, 2019) and chatrooms (Kiyimba & Lester, 2019), amongst many others. Due to increased utilisation of health care settings and the ease of access which online platforms facilitate, clinicians and academics alike extensively explore the efficacy of e-health as a mental health intervention (Rathbone & Prescott, 2017;Rathbone, Clarry & Prescott, 2017).…”
Section: Online Help Seekingmentioning
confidence: 99%
“…In a UK study, Prescott, Hanley & Ujhelyi (2019) explored why young people use online forums for mental health and emotional support. Qualitative analysis found that OMHCs are an invaluable resource for users to turn to when they seek peer-to-peer support.…”
Section: Online Mental Health Communities (Omhc)mentioning
confidence: 99%